Terapi Kognitif Mengungkapkan Perasaan pada Pasien Perempuan di Rumah Sakit Jiwa Pemerintah Aceh - Syarifah Masthura; Melli Afrijayani; Maulidia Maulidia; M. Farisga Tangerang; Sukma Khaira; Abdul Aziz Marzuki; Liza Putri Nabila; Hayaton Nufus; Rahmawati Rahmawati (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2026)
Expressive feelings therapy is a form of mental health nursing modality therapy that aims to help individuals express their thoughts and emotions openly without violating the rights of others. This study aims to explore the effectiveness of cognitive therapy focused on “expressing feelings” in improving emotional expression abilities among female patients in the recovery phase at the Anggrek Ward of the Aceh Government Mental Hospital. This descriptive qualitative study was conducted through group therapy activities with structured stages, using media such as emotion expression picture cards and a spin-the-bottle game as interaction stimuli. The population consisted of 18 patient in the Anggrek ward, with a sample of 12 patients who were cooperative, psychologically stable, able to communicate bidirectionally, and willing to participate in group therapy. The results showed that participants experienced an improvement in their ability to express emotions such as happiness, sadness, anger, and anxiety more openly, accompanied by increased social interaction and reduced emotional tension. The therapy also encouraged greater self-confidence and a sense of emotional relief. These findings support that expressive feelings therapy can be incorporated as part of routine nursing interventions for patients who experience difficulties in emotional regulation. It is recommended that further research be conducted over a longer duration and with a broader scope to strengthen the validity of the findings.